Application of Microsoft Office 365 as English Vocabulary Learning Media for Vocational High School Students - Saly Kurnia Octaviani; Arumsari (Surakarta English and Literature Journal, 2022)
English language learner often deals with the problem of vocabulary learning. Students as second language learner need teacher’s guide to find adequate English vocabulary learning media. This study aimed to analyze the implementation of Microsoft Office 365 for teaching and learning English vocabulary of vocational high school students in SMK Analis Kesehatan Nasional. This study involved 20 students in eleventh grade students with the experience of using Microsoft Office 365 application for two years. By applying descriptive qualitative research, this study used questionnaire to collect the data and explain the result by description. This study presented conclusion that Microsoft Office 365 application is useful for teaching and learning English vocabulary of students in SMK Analis Kesehatan Nasional. This conclusion is based on the questionnaires’ results dealing with students’ English vocabulary comprehension in Microsoft Office 365, influence of Microsoft Office 365 toward students’ English vocabulary, and students’ English vocabulary knowledge in Microsoft Office 365. Dealing the result of questioners, 77,5% students comprehended English vocabulary in Microsoft Office 365 and 97,5% students admitted Microsoft Office 365 influenced students’ English vocabulary. In average of students’ vocabulary knowledge, 71.25% students comprehended 20 English vocabularies on homepage of Microsoft Office 365.